CPC-149 Trimebutine: A Case of Abuse and Possible Dependence. (12th March 2013) - Guillermet, A; Geneste, M; Combe, C; Hida, H
Abstract : Background: Trimebutine has an agonist effect on digestive tract and brain mu, kappa, and delta opiate receptors. Purpose: To describe a case report of an abuse and a possible dependence on trimebutine. Materials and Methods: Medical record review and literature search about trimebutine dependence. Results: A 46-year-old woman with a history of Chronic Intestinal Pseudo-Obstruction (CIPO) was prescribed amikacin and trimebutine in the hospital since 2011. Her gastroenterologist initially prescribed trimebutine at 100 mg intravenously three times a day, with a possibility of 100 mg shots if necessary without a maximum dose. At the same time she obtained another prescription by her general practitioner (50 mg IV if needed). Finally 735 ampoules were delivered in seven weeks (15 a day).This overconsumption alarmed the pharmaceutical team and a literature review was made. Dependence is described in a French register: six cases of intravenous abuse or dependence were reported between 1993 and 2009. At high doses trimebutine is cardiotoxic (bradycardia, rhythm disorders) and neurotoxic (convulsions). We alerted the prescribers and reported this abuse to our pharmacovigilance centre. A questionnaire to evaluate the level of dependence was sent to the general practitioner. Once the general practitioner had been informed, the gastroenterologist alone managed her CIPO treatment and a new prescription was established with a trimebutine posology more consistent with the marketing authorization. Conclusions: Provision from a hospital enabled us to detect the overuse of this drug. Dependence is difficult to prove and drug abuse screening test in the assessment of DSM IV should be used to establish it. No conflict of interest.